2012
DOI: 10.1177/0272431612453650
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Other Drug Use in Middle School

Abstract: The current study examined the impact of supportive social relationships (i.e., teacher support, adult support, school relatedness) and peer victimization on middle school students’ substance use. Over 3,000 middle school students reported on alcohol, cigarette, and marijuana use, supportive social relationships, and instances in which they were the victim of aggressive behavior. Mixed-effects logit regression analyses revealed complementary patterns of results across types of substances. Students who perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 86 publications
0
15
0
Order By: Relevance
“…Each of these results provide support for the study's hypotheses, except for marijuana use, which was not associated with any of the perceived social support variables. These findings are broadly supported by the literature on perceived social support and substance use (Forster et al, 2013;Wormington et al, 2013). When adolescents feel that the people in their lives will be there for them, they not only have a network of people they can turn to in times of stress, but they are better able to cope with negative events, reducing the negative impact of those events (Baldry & Farrington, 2005;Cohen et al, 2000;Davidson & Demaray, 2007;Fox & Boulton, 2005;Holt & Espelage, 2007).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Each of these results provide support for the study's hypotheses, except for marijuana use, which was not associated with any of the perceived social support variables. These findings are broadly supported by the literature on perceived social support and substance use (Forster et al, 2013;Wormington et al, 2013). When adolescents feel that the people in their lives will be there for them, they not only have a network of people they can turn to in times of stress, but they are better able to cope with negative events, reducing the negative impact of those events (Baldry & Farrington, 2005;Cohen et al, 2000;Davidson & Demaray, 2007;Fox & Boulton, 2005;Holt & Espelage, 2007).…”
Section: Discussionmentioning
confidence: 53%
“…The findings revealed that lower perceptions of family, teacher, and peer social support were linked to victimization. Research has also revealed that social support reduces substance use among adolescents who are victims of face-to-face bullying (Forster et al, 2013;Wormington, Anderson, Tomlinson, & Brown, 2013).…”
Section: Perceived Social Supportmentioning
confidence: 99%
“…Emerging evidence also suggests a positive association between bullying victimization and substance use (McGee, Valentine, Schulte, & Brown, 2011; Tharp-Taylor, Haviland, & D'Amico, 2009; Wormington, Anderson, Tomlinson, & Brown, 2013), which may be mediated by internalizing symptoms such as depression (Luk, Wang, & Simons-Morton, 2010). Indeed, victims of bullying are more vulnerable to social alienation, negative mood, psychological distress, and suicidal ideation than non-victims (Cassidy, 2009; Kaltiala-Heino, Fröjd, & Marttunen, 2010; Menesini, Modena, & Tani, 2009).…”
Section: Parenting Styles and Involvement In Bullying Behaviorsmentioning
confidence: 99%
“…As such, cannabis use in adolescents who have chronic negative experiences with peers might be driven by coping and/or affect regulatory mechanisms ( high social avoidance, low reward sensitivity in Figure 1). Published work has linked greater cannabis use in adolescents with peer victimization [67], bullying [6870], and association with marginalized communities that are often targeted for victimization and harassment (e.g., LGBT and gender-minority adolescents) [71]. …”
Section: Peer-related Behavioral Correlates Of Adolescent Cannabis Usementioning
confidence: 99%